ANALISIS BRAND HATE TERHADAP BRAND AVOIDANCE PADA MEREK STARBUCKS KONTEKS ISSUE ISRAEL-PALESTINA - Fajri Gusnadi; Mohamad Efendi; Nurliya Apriyana (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2024)
The aim of this research is to explore the strength of Brand Hate's influence on Brand Avoidance in the context of Starbucks brand amid the Israel-Palestine issue. The study employs a quantitative method to analyze the relationships between the variables. Multiple regression analysis is utilized to examine the effects of Brand Attitude, Subjective Norms, and Anthropomorphic Tendency on Brand Hate, subsequently impacting Brand Avoidance. Primary data is collected through questionnaire distribution among 108 respondents residing in the Jabodetabek area. Subsequently, the data is organized into tabular form and processed using the SPSS statistical software. The findings indicate that Brand Attitude and Subjective Norms significantly influence Brand Hate, confirming the impact of Brand Hate on Brand Avoidance in this research context. However, Anthropomorphic Tendency exhibits a negative influence on Brand Hate. These findings offer crucial insights for brand management, emphasizing the necessity for more effective strategies in handling negative brand perceptions and addressing sensitive issues. The implications of this study underscore the need to mitigate Brand Hate and Brand Avoidance to enhance brand image and maintain consumer loyalty, particularly amidst geopolitical controversies.